2022-RA-936-ESGO Feasibility of laparoscopic extraperitoneal pelvic lymphadenectomy in obese endometrial cancer patients. (20th October 2022) - Hamdy, Mohamed; Fathi, Adel; Gaballa, Khaled
Abstract : Introduction/Background: Objective: To describe the feasibility of extraperitoneal approach to perform complete para-aortic and pelvic lymphadenectomy in patients with endometrial cancer. Theoretically, extraperitoneal approach is technically easier in the obese patient as it naturally creates a bowel-free operative field. Methodology: A prospective descriptive study evaluating laparoscopic extraperitoneal pelvic lymphadenectomy in patients with endometrial cancer, 20 endometrial cancer patients were enrolled in the trial. Results: Result: 2 cases were shifted to open and excluded from the trial. The median BMI of the patients was (37.5), in 3 (16.6%) cases, right nodal dissection was performed through the transperitoneal approach. The average number of pelvic nodal yield was (20). The mean total operative time was 298 (±53.2) minutes. The mean lymphadenectomy time 194.4 (±34.3) minutes. The mean blood loss was 120 (±25.2) ml. the mean hospital stays1.67 (±0.76) days. No patient experienced tumor recurrence with mean follow-up of 12 (±5.6) months. Conclusion: Laparoscopic extraperitoneal pelvic lymphadenectomy is feasible, effective, and safe approach and has an added value when offered to obese females such as cases with endometrial cancer.